2009
DOI: 10.1093/aob/mcp082
|View full text |Cite
|
Sign up to set email alerts
|

Ecological correlates of ex situ seed longevity: a comparative study on 195 species

Abstract: The data suggest that the endospermic seeds of early angiosperms which evolved in forest understorey habitats are short-lived. Extended longevity presumably evolved as a response to climatic change or the invasion of drier areas. The apparent short-lived nature of endospermic seeds from cool wet environments may have implications for re-collection and re-testing strategies in ex situ conservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
330
6
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(373 citation statements)
references
References 23 publications
19
330
6
18
Order By: Relevance
“…The presence of W-box and NF-x regulatory ciselements in the promoter regions of IAA regulating genes CYP79B2 and CYP83B1 and the high number of ARFs in the longevity module provide another link between pathogen-related and developmental roles of auxins and offer a new research area for seed biology. Across 195 species, seed longevity is correlated to seed structure and climate origin but not with seed mass and storage composition, with early angiosperms having short-lived seeds in dry storage (Probert et al, 2009). We hypothesize that seed longevity has evolved by co-opting existing genetic pathways regulating the activation of defense against necrotrophic pathogens to ensure prolonged survival in the dry state to be ready for next generations.…”
Section: Link Between Seed Longevity and Genetic Pathways Regulatingmentioning
confidence: 95%
See 1 more Smart Citation
“…The presence of W-box and NF-x regulatory ciselements in the promoter regions of IAA regulating genes CYP79B2 and CYP83B1 and the high number of ARFs in the longevity module provide another link between pathogen-related and developmental roles of auxins and offer a new research area for seed biology. Across 195 species, seed longevity is correlated to seed structure and climate origin but not with seed mass and storage composition, with early angiosperms having short-lived seeds in dry storage (Probert et al, 2009). We hypothesize that seed longevity has evolved by co-opting existing genetic pathways regulating the activation of defense against necrotrophic pathogens to ensure prolonged survival in the dry state to be ready for next generations.…”
Section: Link Between Seed Longevity and Genetic Pathways Regulatingmentioning
confidence: 95%
“…These traits rely on the remarkable capacity of seeds to undergo complete desiccation without loss of viability (desiccation tolerance [DT]) and to remain alive for extended periods of time when stored in the dry state (longevity) . While DT is acquired during seed filling, longevity progressively increases during the final phase of seed maturation (Probert et al, 2009;Chatelain et al, 2012). Seed longevity is the ultimate survival mechanism for the plant in order to bridge unfavorable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Further recent evidence that the longevity of orchid seeds is poor relative to those of other species can be drawn from the increasingly large body of data on the longevity of orthodox seeds of agricultural and wild species (Walters et al 2005;Kochanek et al 2009;Probert et al 2009;Tuckett et al 2010;Mondoni et al 2011). Much of this data is based on the application of rapid-aging techniques, whereby seeds are stored at elevated temperature and RH, usually at 45Њ or 60ЊC and 60% RH (Newton et al 2009).…”
Section: Orchid Seed Storage Behaviormentioning
confidence: 99%
“…Much of this data is based on the application of rapid-aging techniques, whereby seeds are stored at elevated temperature and RH, usually at 45Њ or 60ЊC and 60% RH (Newton et al 2009). During these controlled aging experiments, seeds are retrieved from storage periodically and assessed for viability, with the longevity of species ranked relative to each other, most commonly via comparing the time for 50% seed viability loss (p 50 ; Probert et al 2009;Tuckett et al 2010;Mondoni et al 2011). This approach assumes that seed aging kinetics at high temperature and RH are the same as those when seeds are stored under cool (e.g., Ϫ20ЊC), dry (e.g., 15% RH) conditions, and although this correlation is yet to be verified because of a scarcity of data from long-term studies (Walters et al 2005), a highly significant relationship has been shown to occur between families aged under standard seed banking protocols and those aged under controlled aging conditions ).…”
Section: Orchid Seed Storage Behaviormentioning
confidence: 99%
“…O conhecimento das diferenças da longevidade das sementes é fundamental para o manejo adequado dos bancos de sementes e, no caso das espécies não cultivadas, particularmente importante, considerando a heterogeneidade genética das populações, e qualquer decréscimo significativo na viabilidade resultará na perda de genótipos dos acessos armazenados (PROBERT et al, 2009).…”
Section: Introductionunclassified